Revalidation and genetic characterization of new members of Group C (Orthobunyavirus genus, Peribunyaviridae family) isolated in the Americas - Nunes, Márcio Roberto Teixeira (PLoS One, 2018)
Group C serogroup includes members of the Orthobunyavirus genus (family Peribunyaviridae) and comprises 15 arboviruses that can be associated with febrile illness in humans. Although previous studies described the genome characterization of Group C orthobunyavirus, there is a gap in genomic information about the other viruses in this group. Therefore, in this study, complete genomes of members of Group C serogroup were sequenced or re-sequenced and used for genetic characterization, as well as to understand their phylogenetic and evolutionary aspects. Thus, our study reported the genomes of three new members in Group C virus (Apeu strain BeAn848, Itaqui strain BeAn12797 and Nepuyo strain BeAn10709), as well as re-sequencing of original strains of five members: Caraparu (strain BeAn3994), Madrid (strain BT4075), Murucutu (strain BeAn974), Oriboca (strain BeAn17), and Marituba (strain BeAn15). These viruses presented a typical genomic organization related to members of the Orthobunyavirus genus. Interestingly, all viruses of this serogroup showed an open reading frame (ORF) that encodes the putative nonstructural NSs protein that precedes the nucleoprotein ORF, an unprecedented fact in Group C virus. Also, we confirmed the presence of natural reassortment events. This study expands the genomic information of Group C viruses, as well as revalidates the genomic organization of viruses that were previously reported.